Comparison of effect and mechanism between nalfurafine hydrochloride and narrow-band ultraviolet B phototherapy in the treatment of pruritus in hemodialysis patients - Sooyeon Choi; Dong Hui Shin; Jae-Seok Kim; Jun Young Lee; Seung Ok Choi; Byoung-Geun Han; Eun Jung Kim; Eung-Ho Choi; Jae Won Yang (Annals of Medicine)
Objectives Pruritus in hemodialysis patients (HDP) is one of the serious complications associated with the quality of life and psychiatric disorder of patients. The narrowband ultraviolet B phototherapy (NB-UVB) treatment showed a statistically significant reduction of itching when performed more than 4 times compared to conservative treatment for itching, and the difference was confirmed to increase with repetition. We aim to compare newly developed Nalfuranfine HCL, kappa-opioid receptor agonist, with NB-UVB in HDP.Methods Twenty HDP were enrolled from Wonju severance Christian hospital. Visual analog scale (VAS) score, Shiratori score, skin inflammatory cytokine levels, and blood calcium/phosphate/vitamin D levels were measured before four weeks of treatment, during four weeks of treatment, and after four weeks of treatment.Results VAS and Shiratori score was reduced in both nalfurafine and NB-UVB treatment groups significantly. After four weeks of treatment, the NB-UVB treatment group maintained a low Shiratori score, however, the Shiratori score increased in nalfurafine treatment group. Calcium phosphate product concentration was increased in the UVB treatment group and decreased in the nalfurafine treatment group. Vitamin D level was increased only in the UVB treatment group. Skin inflammatory cytokines levels showed a decreasing trend in both groups but not statistically significant. There were no side effects in both treatment groups.Conclusions Nalfurafine could be an alternative treatment option compared with NB-UVB as an oral medication in pruritis in hemodialysis patients, especially those with hyperphosphatemia